Pour some sugar on it: the expanding world of bacterial protein O‐linked glycosylation. Issue 1 (12th June 2013) - Iwashkiw, Jeremy A.; Vozza, Nicolas F.; Kinsella, Rachel L.; Feldman, Mario F.
Summary Protein glycosylation was once considered as an eccentricity of a few bacteria. However in the recent years multiple O‐glycosylation mechanisms have been identified in bacterial species from the most diverse genera, including various important human pathogens. This review focuses on summarizing the structural diversity, the various pathways and the physiological roles of this post‐translational protein modification. We propose a classification of O‐glycosylation based on the requirement of an oligosaccharyltransferase (OTase). OTase‐dependent glycosylation utilizes an oligosaccharide synthesized on a lipid carrier that is transferred to proteins en bloc by an OTase. Multiple proteins, including the pilins, are glycosylated using this mechanism. OTase‐independent glycosylation refers to the pathway in which glycosyltransferases sequentially add monosaccharides onto the target proteins. This pathway is employed for glycosylation of flagella and autotransporters. Both systems play key roles in pathogenesis. Exploiting glycosylation machineries it is now possible to generate glycoconjugates made of different proteins attached to polysaccharides derived from LPS or capsule biosynthesis. These recombinant glycoproteins can be exploited for vaccines and diagnostics of bacterial infections. Furthermore, O‐glycosylation systems are promising targets for antibiotic development. Technological advances in MS and NMR will facilitate the discovery of novel glycosylation systems. Likely, the O‐glycosylation pathways we currently know constitute just the tip of the iceberg of a still largely uncharacterized bacterial glycosylation world.